Interconnection between the Chinese Nominal Classifiers and Nouns - Maohua, Ni (Sinología hispánica. China Studies Review, 2026)
According to the perspective of the linguistics typology, Chinese is one of the languages with classifiers system while Spanish is not. This is one of the factors that make the Spanish-speaking students feel difficult to handle the collocations of Chinese classifiers and the nouns they measure or quantify. What confuses learners most exists in the mutual selection motivations between classifiers and nouns. In these seemingly arbitrary motivations, cognitive mechanisms that reflect the way of feeling and expressing the real world with a linguistic system does work. With the analysis of the cognitive models of the syntactic structure of the classifier, this paper studies the interconnecting relationships between nominal classifiers and nouns of Chinese from the perspective of cognitive linguistics, in order to help the Spanish-speaking students to understand and manage the uses of the nominal classifiers.